Lives in play : autobiography and biography on the feminist stage - Claycomb, Ryan M., 1974- (University of Michigan Press, 2012)
"Lives in play explores the centrality of life narratives to women's drama and performance from the 1970s to the present moment. In the early days of second-wave feminism, the slogan was 'The personal is the political.' These autobiographical and biographical 'true stories' have the political impact of the real and have also helped a range of feminists tease out the more complicated aspects of gender, sex, and sexuality in a Western culture that now imagines itself to be 'postfeminist.' The book covers a broad range of texts and performances, from performance artists like Karen Finley, Holly Hughes, and Bobby Baker to playwrights like Suzan-Lori Parks, Maria Irene Fornes, and Sarah Kane. The book examines biography and autobiography together to link their narrative tactics and theatrical approaches and show the persistent and important uses of life writing strategies for theater artists committed to advancing women's rights and remaking women's representations. Lives in play argues that these writers and artists have not only responded to the vibrant conversations in feminist theory but also have anticipated and advanced these ideas, theorizing gender onstage for specific ends. Ryan Claycomb demonstrates how these performances work through tensions between performative identity and the essentialized body, between the truth value of life stories and the constructed nature of gender and narrative alike, and between writing and performing as modes of feminist representation. The book will appeal to scholars in performance studies, women's studies, and literature, including those in the growing field of auto/biography studies."--Jacket.